Bioconversión de las Ellagitanninas melas tropical de montaña (Rubus adenotrichos) y relación con la ecología del microbiomo intestinal - García Muñoz, María Cristina (Montpellier SupAgro, 2018)
Consumption of dietary ellagitannins (ETs) could be associated mainly with prevention of cardiovascular diseases and regulation of hormone-dependent cancers. Nonetheless, ETs are not bioavailable as such; therefore, after being partially converted into ellagic acid (EA) in the upper gastrointestinal (GI) tract, they undergo sequential bioconversion in the colon by gut microbiota into urolithins, a more bioavailable and bioactive group of molecules that persist up to 4 days at relatively high concentrations in urine. Variability of urolithin excretion in urine is high and three main groups, “no or low urolithin excreters,” “predominantly UA derivatives excreters” and “predominantly UB derivatives excreters,” were observed on a cohort of 26 healthy volunteers.